In vitro Anti-Helicobacter pylori Activity of Capsaicin - Department of Pharmaceutical Sciences, Faculty of Pharmacy, University of Jordan, Amman, Jordan. (19672696) (2020)
Worldwide, peptic ulcer and gastritis considered to be one of the biggest health challenge, Helicobacter pylori is responsible for more than eighty percent of chronic active gastritis where continual infection remains for decennary. However, the success of commercially available drugs for the management of H. pylori has overwhelmed by antibiotic-resistant strains, especially, metronidazole and clarithromycin, therefore, an urgent need arise to search for new options for treatment with enhanced anti- H. pylori activities, while being less toxic to human cells. Naturally occurring plant products, including spices, are one of these strategies that showed activity against H. pylori. Present study aim to test the antibacterial activity of capsaicin and other pure plant-derived compounds against a standard (NCTC 11916) H. pylori strain In vitro and to test for possible synergistic effect when combined with conventional therapy. Capsaicin shows good antibacterial activity on regular antimicrobial sensitivity testing methods (Anti-MSTM) and titration checkerboard assay MIC (0.0625 mg/ml), whereas piperine MIC was (0.125 mg/ml). While for curcumin no inhibition was found. The strain was found to be resistant to metronidazole with (MIC=250 μg/ml). When combining capsaicin with metronidazole, (FIC) Fractional inhibitory concentration values shown a synergistic effect, While the additive effect was found for capsaicin combination with piperine. Our obtained data indicate that capsaicin possesses promising anti H. pylori bioactivity and synergistic activity when combined with metronidazole but more work is necessary to examine the mechanisms by which these happened. Furthermore, it is necessary to ensure its activity against H. pylori In vivo and clinical settings. Other Information Published in: Journal of Pure and Applied Microbiology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.22207/jpam.14.1.29